Pengaruh Pertumbuhan Ekonomi, Investasi Asing, Inflasi, dan Trade Openness terhadap Ketimpangan di Indonesia Tahun 2000-2020 - Erni Sri Wijayanti; Siti Aisyah (Universitas Batanghari Jambi, 2022)
A big problem faced by developing countries such as Indonesia is the income gap between people with high incomes and people with low incomes, a condition that if left unchecked will hamper the development process. There are several factors that cause high income inequality in Indonesia, some of which will be analyzed in this study, namely economic growth, foreign investment, inflation and Trade Openness or trade openness. The study was conducted to determine the effect of these variables on income inequality in Indonesia during the period 2000-2020. The data used is sourced from the World Bank with the Ordinary Least Square (OLS) regression method. The results of the study found that economic growth and foreign investment had a positive effect on income inequality, Trade Openness had a negative effect on income inequality, while inflation had no effect on income inequality in Indonesia. To reduce inequality, economic development outside the Java-Bali-Sumatra Region, especially in Eastern Indonesia, must be the main focus of the Indonesian government. Policies on investment in infrastructure development, especially those related to the smooth flow of logistics or connectivity, are key targets for reducing inequality. Redistribution policies, such as taxes and transfer assistance must be carried out with the principle of efficiency, because they are the first remedy in overcoming the problem of inequality.